Data loggers in artificial eggs reveal that egg-turning behavior varies on multiple ecological scales in seabirds. (29th March 2017) - Clatterbuck, Corey A.; Young, Lindsay C.; VanderWerf, Eric A.; Naiman, Alexander D.; Bower, Geoff C.; Shaffer, Scott A.
Abstract: In most avian species, egg-turning behavior during incubation is vital for proper embryonic development and hatching success. However, changes in turning behaviors are rarely studied across different temporal scales (e.g., day–night or across incubation phases), though the timing of incubation behaviors affects reproductive success. We used data loggers encapsulated in artificial eggs to measure turning rates and angle changes of eggs in Western Gull ( Larus occidentalis ) and Laysan Albatross ( Phoebastria immutabilis ) nests. We examined diurnal and daily cycles in egg-turning behaviors across early, middle, and late incubation phases. Our results indicate that (1) egg-turning behaviors remain similar throughout incubation, resulting in a consistent environment for developing chicks; (2) egg-turning rates and angle changes vary according to diurnal cycles and day length in each species; and (3) egg-turning rates, but not angle changes, were similar between species. Egg-turning behaviors may vary among species according to seasonality and geography, and using consistent methodologies to measure egg turning will further clarify the role of egg turning in avian life history and ecology.